Viability of astrotourism in South African National Parks as a revenue source for conservation - Amélia S. Wassenaar; Brenda A. Coetzee (Koedoe: African Protected Area Conservation and Science, 2025)
South African National Parks (SANParks) face increasing pressure to generate revenue from tourism. Astrotourism has been identified as a potential low-impact income generating activity suitable for parks. However, SANParks need to understand the potential elements impacting on viability of astrotourism prior to development of such activities. The aim of the study was to explore the viability of low environmental impact astrotourism activities in SANParks to generate income based on important economic and practical considerations. A mixed-methods approach, using responses from 1150 participants in quantitative online surveys, combined with insights obtained through qualitative semi-structured interviews with 13 stakeholders in SANParks and 42 semi-structured interviews with stakeholders of global astrotourism initiatives, was used. Results from the online survey indicated that a demand exists for astrotourism activities in parks. Interest in astrotourism activities appealed to a wide range of respondents, from those with limited knowledge of astronomy to experts in the field. Tourists prefer authentic astrotourism experiences that have a low environmental impact and are not over-commercialised. The economic viability of astrotourism activities in parks was determined by considering demand and willingness to pay, while practical concerns derived from stakeholder interviews included suitable locations, availability of resources, expectations of the experience and challenges to be mitigated. In conclusion, astrotourism activities, if developed with these considerations, can be viable income-generating opportunities to generate direct income for SANParks and add value to the regional economy.